AN ERROR ANALYSIS ON EFL STUDENT’S REFLECTIVE JOURNAL WRITING ON ONLINE BLOGGING AT TARBIYA AND TEACHERS TRAINING FACULTY STATE ISLAMIC UNIVERSITY OF NORTH SUMATERA - Kurniati, Eka Yuni (Faculty of Tarbiyah nad Teacher Training, 2021)
The aim of this study was to find out: 1) the kinds of error made by EFL student’s reflective journal writing on online blogging, 2) the process that the EFL student did in producing errors, 3) the causes of error happened on EFL student's reflective journal writing. This study was categorized into a qualitative content analysis. The data of this study were 10 reflective journal writings of EFL student on her blogging account and the data source was one of the EFL students of State Islamic University of North Sumatera. The data were observed by purposive sampling. Thus for the results of this study, the researcher found five kinds of errors that appeared on EFL student’s reflective journal writing on her online blogging. They were; error in time, omission error, insertion error, part of speech error and other errors. The errors happened unconsciously, the EFL student made errors by eliminating, adding some unnecessary word and disordering some words in arranging sentence. There were several factors behind the occurrence of errors, namely Interlingua transfer, intralingua transfer, lack of vocabulary, and the use of inappropriate translate techniques. Keywords: Error Analysis, Reflective Journal, Online Blogging, and Surface Strategy Taxonomy